Features of formation of pathological urge to gamble depending on alexithymia, in the conditions of stress of COVID-19 pandemic - Salnikova, Alina; Chaban, Олег (Psychosomatic Medicine and General Practice, 2020)
Introduction. The COVID-19 pandemic may exacerbate mental health problems in the general population, including increasing involvement in addictive behavior. Recent observations suggest that the current crisis and its consequences may exacerbate gambling problems. There are a number of English-language studies with a fundamental analysis of the accumulated knowledge on the causes of pathological gambling and stress-related problems, but the analysis of accumulated in recent years data from the domestic scientific literature on this problem has not yet been done. A clear understanding of the relationship between alexithymia and pathological gambling in the stressful pandemic of the COVID-19 pandemic is a prerequisite for further research to develop new approaches to therapy. Need advice and recommendations for the general public and for professionals. Important national or local references to information on treatment and support options, including those that can be performed remotely. Goal. To determine the current state of analysis of the peculiarities of the formation of pathological cravings for gambling depending on alexithymia, to systematize the data and compare the information presented in the Ukrainian and foreign scientific literature on this issue in recent years. Materials and methods. A qualitative and quantitative content analysis of scientific Ukrainian and English literature, published until 2019, was conducted, which sets out different views on the peculiarities of the formation of pathological craving for gambling depending on alexithymia. The search was performed using PubMed, Web of Science and Scopus databases. To analyze the views of world researchers on the peculiarities of the formation of pathological gambling addiction depending on alexithymia, it was decided to include only review articles, concept analyzes, meta-analyzes, systematic reviews published in English, presented in the scientific literature. All studies evaluated alexithymia on the TAS scale - Toronto alexithymia scale, while gambling was assessed mainly using the SOGS scale - South Oaks Gambling Screen. Conclusions. The data found in this review suggest that alexithymia should be considered in the clinical evaluation of gambling. Because alexithymia has been found to respond positively to psychological interventions, and gambling problems can also be effectively reduced through multiple care strategies, assessing alexithymia in these subjects can help plan more effective individualized treatment protocols. Gamers may find it helpful to focus on recognizing and understanding their own emotional states and developing more adaptive ways to manage their feelings.